Photothermal Coating on Zinc Alloy for Controlled Biodegradation and Improved Osseointegration - Yuchien Hsu; Yunjiao He; Xiao Zhao; Feilong Wang; Fan Yang; Yufeng Zheng; Yongsheng Zhou; Dandan Xia; Yunsong Liu (Advanced Science)
Abstract Zinc (Zn) and its alloys are promising biomaterials for orthopedic applications due to their degradability and mechanical properties. Zn2+ plays a crucial role in bone formation, but excessive early release may cause cytotoxicity and inhibit osseointegration. To solve this, we developed a near‐infrared (NIR) light‐controlled polycaprolactone/copper‐sulfur (PCL/CuS) coating that slows degradation and enhances osseointegration of Zn alloys. The zinc–lithium (Zn–Li) substrate is encapsulated with PCL, reducing Zn2+ release and maintaing biocompatibility. Controlled Zn2+ release and mild photothermal therapy via CuS nanoparticles promoted osteogenesis. In vitro studies demonstrated enhanced cell proliferation and osteogenic differentiation. In vivo Micro‐Computed Tomography (Micro‐CT), Scanning Electron Microscopy‐Energy Dispersive Spectroscopy (SEM‐EDS), and immunohistochemical analyses confirmed improved osseointegration. Mechanistic studies using RNA sequencing and Western blotting revealed that the coating promotes osteogenesis by activating the Wnt/β‐catenin and inhibiting NF‐κB pathways. This NIR light‐controlled PCL/CuS coating successfully regulates Zn alloy degradation, enhances osseointegration via controlled Zn2+ release and mild photothermal therapy effct, presenting a promising avenue for orthopedic biomaterials.